2022
DOI: 10.3390/genes13020379
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium Is Enriched in Gut Microbiome of Kashmiri Women with Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a very common endocrine condition in women in India. Gut microbiome alterations were shown to be involved in PCOS, yet it is remarkably understudied in Indian women who have a higher incidence of PCOS as compared to other ethnic populations. During the regional PCOS screening program among young women, we recruited 19 drug naive women with PCOS and 20 control women at the Sher-i-Kashmir Institute of Medical Sciences, Kashmir, North India. We profiled the gut microbiome in fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…At the order level, 2 taxa showed significant differences ( Supplementary Table S7 ), with an increase in Bacillales ( Mammadova et al, 2021 ) and a decrease in ML615J-28 ( Lindheim et al, 2017 ) in PCOS patients. At the family level, we identified 50 taxa with significant differences ( Supplementary Table S8 ), with 37 taxa significantly enriched ( Jobira et al, 2020 ; Mammadova et al, 2021 ; Zhu et al, 2021 ; Hassan et al, 2022 ; Yu et al, 2022 ) and 12 taxa significantly reduced ( Lindheim et al, 2017 ; Jobira et al, 2020 ; Dong et al, 2021 ; Zhu et al, 2021 ; Hassan et al, 2022 ; Yu et al, 2022 ) in PCOS patients, but one bacterial taxon showed controversial results. Eyupoglu et al (2020) found that Ruminococcaceae increased in PCOS patients, but two other studies concluded the opposite ( Liu et al, 2017 ; Zhu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the order level, 2 taxa showed significant differences ( Supplementary Table S7 ), with an increase in Bacillales ( Mammadova et al, 2021 ) and a decrease in ML615J-28 ( Lindheim et al, 2017 ) in PCOS patients. At the family level, we identified 50 taxa with significant differences ( Supplementary Table S8 ), with 37 taxa significantly enriched ( Jobira et al, 2020 ; Mammadova et al, 2021 ; Zhu et al, 2021 ; Hassan et al, 2022 ; Yu et al, 2022 ) and 12 taxa significantly reduced ( Lindheim et al, 2017 ; Jobira et al, 2020 ; Dong et al, 2021 ; Zhu et al, 2021 ; Hassan et al, 2022 ; Yu et al, 2022 ) in PCOS patients, but one bacterial taxon showed controversial results. Eyupoglu et al (2020) found that Ruminococcaceae increased in PCOS patients, but two other studies concluded the opposite ( Liu et al, 2017 ; Zhu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…As usual, data that demonstrate the absence of a difference between patients with PCOS and the control group were obtained from the research that studied the association of gut microbiota with obesity, and the patients with and without PCOS were not stratified by this important comorbidity [ 8 , 11 , 15 , 20 ]. Among the publications currently available for analysis, we found four studies in which the authors note higher values of all indexes analyzed or at least one index in patients with PCOS compared with the control group [ 9 , 20 , 24 , 29 ]. In all these studies, the authors revealed the relationships of the clinical parameters with the species composition of the gut microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, a hypothesis called DOGMA (dysbiosis of gut microbiota, intestinal microbiota dysbiosis) suggested that intestinal dysbiosis can lead to chronic inflammation, insulin resistance, and androgen hypersecretion, which, in turn, are associated with PCOS [ 6 ]. In regard to this hypothesis, the associative relationship between the intestinal microbiota and various pathological conditions and indicators in patients with PCOS is being actively studied ( Table S1 ) [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Collinsella and Bifidobacterium have been reported to be associated with PCOS. 33 PCOS has been reported to be caused by increased secretion of androgens, 61 suggesting that Collinsella and Bifidobacterium may be involved in the secretion of hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also clarified that the characteristics of the human gut microbiota are influenced by several factors, such as age, sex, and dietary habits of the hosts. [30][31][32] Polycystic ovarian syndrome (PCOS), a gynecological disease like PMS, has been reported to be associated with Bifidobacterium, 33 and uterine fibroids with Pseudomonas stutzeri and Prevotella amnii. 34 This led us to consider that PMS, which is thought to be caused by female hormones 35 and diet [36][37][38] may also be associated with the gut microbiota, like other diseases.…”
Section: Introductionmentioning
confidence: 99%